2019
DOI: 10.1002/ejic.201900967
|View full text |Cite
|
Sign up to set email alerts
|

Metallo‐Corroles Supported on Carbon Nanostructures as Oxygen Reduction Electrocatalysts in Neutral Media

Abstract: In this work, we report the investigation of Fe and Co triphenylcorrole complexes supported on two different carbon supports as eletrocatalysts for the ORR in neutral pH media, comparing their performances with the corresponding tetraphenylporphyrin complexes. Cyclic voltammetry experiments were acquired in neutral phosphate buffer demonstrating that corroles exhibit a superior catalytic activity towards ORR than porphyrins, as demonstrated by more positive oxygen reduction peak potential (E pr ) and half-wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This similar electrochemical behavior can be attributed to the use of FePc on the surface of carbon support. That is, the role of carbon support consists specially on the improvement of active sites, in the keep stick open the Femacrocycle and avoiding the aggregation phenomena typical of FePc without support [79,83,86,87]. In addition, other characteristic of carbon support to facilitate the electrochemical performance of composites is the presence of Nfunctionalities and high structural defects and conductivity, in terms of charge dispersion, stability through the π-π interaction, and increasing overpotential ORR [34,56,65,66].…”
Section: Discussion and Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This similar electrochemical behavior can be attributed to the use of FePc on the surface of carbon support. That is, the role of carbon support consists specially on the improvement of active sites, in the keep stick open the Femacrocycle and avoiding the aggregation phenomena typical of FePc without support [79,83,86,87]. In addition, other characteristic of carbon support to facilitate the electrochemical performance of composites is the presence of Nfunctionalities and high structural defects and conductivity, in terms of charge dispersion, stability through the π-π interaction, and increasing overpotential ORR [34,56,65,66].…”
Section: Discussion and Comparison With Existing Literaturementioning
confidence: 99%
“…The electrode rotation rate was 1600 rpm. The ORR kinetic current density (J k ) was determined from the Koutecky-Levich equation at 0.9 V, removing background current and normalizing to the electrode geometric area [83]. The RRDE setup is used to measure the current density produced by the disk (J disk ) but also the current density of the ring (J ring ) to quantify the intermediate (HO 2…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Studies have shown that the stability of high‐valent metal–oxo intermediates greatly affects the catalytic performance of ORR. [ 95–97 ] The corrole ring exhibits three protons instead of two, which allows corrole to stabilize high‐oxidation‐state transition metals. Recent studies on metal corroles have found that when the central metal ion was Co(III), the catalyst exhibited the highest ORR activity.…”
Section: Carbon Nanotube/mmc Orr Catalystsmentioning
confidence: 99%
“…[ 97,98 ] The ORR activity of CNT‐supported Co(III) corroles in acidic, alkaline, and neutral electrolytes has been reported in many studies. [ 95,99–101 ] For example, Meng et al. controlled the interaction between corroles and CNTs by adjusting the corrole β substituents to optimize the catalytic properties ( Figure 6 a).…”
Section: Carbon Nanotube/mmc Orr Catalystsmentioning
confidence: 99%
“…In this context, many studies have been addressed to develop alternative catalysts to noble metals (i.e., platinum), which are expensive, rare and sensitive to poisoning [3,8]. Platinum-group-metal-free (PGM-free) catalysts represent a very promising category of new catalysts due to their tuneable composition based on transition metals (Fe, Ni, Co, Mn, Cu) supported on carbon substrates (graphene, graphene oxide, carbon nanotubes, black pearls, carbon black and biochar), which are also doped with heteroatoms (N, P, S, O) [12][13][14][15][16][17][18][19][20] Among PGM-free catalysts, metal-nitrogen-carbon (M-N-C) materials have been widely investigated toward ORR in acidic and alkaline pH, whereas the study of ORR in neutral media still accounts for few reports [6,8,12,21,22]. So far, attention has been paid to the development of Fe-N-C catalysts, and the efficiency of active sites in Fe-N-C composites has been ascribed to the coordination of iron to nitrogen heteroatoms in FeNx structure, which cause a beneficial effect on the direct conversion of oxygen to water via a four-electron mechanism [1,8,10,18].…”
Section: Introductionmentioning
confidence: 99%